Abi induces ectopic sensory organ formation by stimulating EGFR signaling. - Stephan, R.; Grevelhörster, A.; Wenderdel, S.; Klämbt, C.; Bogdan, S. (Mechanisms of Development, 2008)
One of the central regulators coupling tyrosine phosphorylation with cytoskeletal dynamics is the Abelson interactor (Abi). Its activity regulates WASP-/WAVE mediated F-actin formation and in addition modulates the activity of the Abelson tyrosine kinase (Abl). We have recently shown that the Drosophila Abi is capable of promoting bristle development in a wasp dependent fashion. Here, we report that Drosophila Abi induces sensory organ development by modulating EGFR signaling. Expression of a membrane-tethered activated Abi protein (Abi(Myr)) leads to an increase in MAPK activity. Additionally, suppression of EGFR activity inhibits the induction of extra-sensory organs by Abi(Myr), whereas co-expression of activated Abi(Myr) and EGFR dramatically enhances the neurogenic phenotype. In agreement with this observation Abi is able to associate with the EGFR in a common complex. Furthermore, Abi binds the Abl tyrosine kinase. A block of Abl kinase-activity reduces Abi protein stability and strongly abrogates ectopic sensory organ formation induced by Abi(Myr). Concomitantly, we noted changes in tyrosine phosphorylation supporting previous reports that Abi protein stability is linked to tyrosine phosphorylation mediated by Abl.